Metallurgical Review of Al-Cu Friction Welded Joints - Nidya Jullanar Salman (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2026)
Friction welding of aluminum and copper is a solid-state joining technique widely used in electrical and industrial applications. Significant differences in physical and thermal properties between these metals create challenges at the joint interface. This review focuses on the metallurgical characterization of Al–Cu friction welded joints, emphasizing intermetallic compound (IMC) formation and growth, and the influence of process parameters such as temperature, pressure, friction time, and rotational speed on microstructure and mechanical performance. Excessive IMC layers can cause embrittlement, interfacial cracking, porosity, and reduced thermal stability. Recent advances in process optimization, active cooling, and interface engineering have improved joint strength, ductility, and conductivity. Controlling IMC growth and understanding intermetallic diffusion are crucial for producing reliable Al-Cu joints. This review summarizes current strategies for enhancing the mechanical performance of Al–Cu friction welded joints.